Comparing computed tomography localization with daily ultrasound during image‐guided radiation therapy for the treatment of prostate cancer: a prospective evaluation - Feigenberg, Steven J. (J Appl Clin Med Phys, 2007)
In the present paper, we describe the results of a prospective trial that compared isocenter shifts produced by BAT Ultrasound (Nomos, Sewicky, PA) to those produced by a computed tomography (CT) unit in the treatment room to aid in positioning during image‐guided radiation therapy. The trial included 15 consecutive patients with localized prostate cancer. All patients underwent CT and MR simulation immobilized supine in an Alpha Cradle and were treated with intensity‐modulated radiation therapy. BAT Ultrasound was used daily to correct for interfraction motion by obtaining shift in the x, y, and z directions. Two days per week during therapy, CT scans blinded to the ultrasound shifts were obtained and recorded. We analyzed 218 alignments from the 15 patients and observed a high level of correlation between the CT and ultrasound isocenter shifts (correlation coefficients: 0.877 anterior–posterior, 0.842 lateral, and 0.831 superior–inferior). The systematic differences were less than 1 mm, and the random differences were approximately 2 mm. The average absolute differences, including both systemic and random differences, were less than 2 mm in all directions. The isocenter shifts generated by using a CT unit in the treatment room correlate highly with shifts produced by the BAT Ultrasound system. PACS numbers: 87.53, 87.59.fm, 87.63.Df